Prognostic value of body composition on survival outcomes in melanoma patients receiving immunotherapy - Kuang, Tianrui; Zhang, Lilong; Qiu, Zhendong; Zhang, Yanbing; Wang, Weixing (Frontiers in Immunology, 2023)
The influence of body composition on the effectiveness of immune checkpoint inhibitors (ICIs) in patients with melanoma is still uncertain in clinical practice. Therefore, the objective of this study was to examine the potential association between body composition and clinical outcomes in patients with melanoma undergoing ICIs treatment.Methods: A systematic literature search was performed across several databases, including PubMed, Embase, Cochrane Library and Google Scholar, to gather relevant studies. The primary outcomes of interest were overall survival (OS) and progression-free survival (PFS), assessed by hazard ratios (HR).Secondary outcomes, such as adverse events (AE), were evaluated using odds ratios (OR).Results: This meta-analysis comprised ten articles involving a total of 1,283 patients. Systemic analysis of all collected evidence revealed that body composition, including low skeletal muscle index (SMI)